PROFIL HEMATOLOGI PADA PENDERITA TUBERKULOSIS SEBELUM DAN SESUDAH PENGOBATAN OAT DI PUSKESMAS KOTA DENPASAR - I Gusti Agung Ayu Satwikha Dewi; Ida Ayu Manik Partha Sutema; Ni Putu Widiantari; Ni Putu Diah Monica Yanti; Ni Ketut Sari Merta Dewi (LPPM Universitas Abdurrab, 2025)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis that attacks the lungs as well as several systems such as gastrointestinal, central nervous, and liver. TB cases have become a global issue, in 2022 Bali has 3,040 cases and Denpasar City has the highest number reaching 1,063 cases. TB treatment is crucial to be handled effectively and efficiently. Examination of hematologic profiles provides important information about the impact of TB and response to treatment. Currently, there is little information on the relationship between hematology profile and OAT treatment of TB patients at the primary health care level such as puskesmas. The purpose of this study was to examine the hematological profile of TB patients before and after OAT treatment at the Denpasar City Health Center. The sampling technique in this study was accidental sampling conducted at the Denpasar City Health Center in January-September 2024. This study was a prospective cohort study supported by literature review. Hematology profile examination of 32 EDTA blood samples was examined using a hematology analyzer including hemoglobin, erythrocyte, leukocyte, platelet, and ESR profiles. Paired T-test results showed that the four hematological profiles had a sig. value smaller than 0.05 (p<0.05), indicating that there was a significant difference between the hematological profiles of TB patients before and after OAT treatment at the Denpasar City Health Center.